2017
DOI: 10.4236/ojg.2017.711113
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Gold Deposits, Geodynamics and Conditions of Formation: A Perspective View

Abstract: Gold occurs in a wide range of deposit types and settings. In the last decade, significant progress has been made in the definition, classification, characterization, thereby aiding understanding of the main gold deposit types. The present work aims to provide an update on the current state of knowledge on the different types of gold deposits models, geodynamics, their mode of formation and the condition suitable for their formation Several subsets of gold deposits are distinguished from one another on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…For gold-quartz veins GIT deposits localized in granitoids, the structure of native gold is coarse-grained with rare simple and polysynthetic twins and patchy heterogeneity, presumably associated with the incorporation of microparticles of native Bi, which, unlike gold, undergoes intense etching even in air (Figure 7). A similar type of patchy heterogeneity for gold from deposits in granitoids was previously described in [8].…”
Section: Internal Structuressupporting
confidence: 69%
See 1 more Smart Citation
“…For gold-quartz veins GIT deposits localized in granitoids, the structure of native gold is coarse-grained with rare simple and polysynthetic twins and patchy heterogeneity, presumably associated with the incorporation of microparticles of native Bi, which, unlike gold, undergoes intense etching even in air (Figure 7). A similar type of patchy heterogeneity for gold from deposits in granitoids was previously described in [8].…”
Section: Internal Structuressupporting
confidence: 69%
“…V.M. Kreiter's followers continued working in this direction [3][4][5][6][7][8]. They showed that the geological and industrial grouping of deposits is determined by their geological homogeneity and belonging to certain gold formations-groups of deposits with a similar material composition of ores and genesis.…”
Section: Introductionmentioning
confidence: 99%
“…Two main stages of the formation of gold deposits are identified in the north-eastern part of the Fennoscandian Shield, the Neoarchean and the Paleoproterozoic, and these stages correspond well to the main global stages of gold deposit formation in the Precambrian (2.7-2.5 and 2.1-1.8 Ga [87][88][89][90]). The Paleoproterozoic stage was more important in the region, as, at this stage, the gold deposits formed not only in the Proterozoic greenstone belts, but in those Archean belts as well, which were involved in the Svecofennian tectonic processes in Paleoproterozoic.…”
Section: Discussionmentioning
confidence: 67%
“…The highest gold concentrations (up to 230 ppm) have been observed within the Papua New Guinea economic zone near Lihir Island [17]. The maximum Au content in this deposit is comparable to the content in bonanza gold deposits [3].…”
Section: Introductionmentioning
confidence: 72%
“…The sources of gold deposits are rocks with gold concentrations exceeding those of the earth's crust contents by 2-3 times or more. In nature, there are several mechanisms for the extraction and transport of gold from the mantle and from rocks of various geneses by hydrothermal fluids, including from lithified marine deposits, starting with the Precambrian [2,3]. At the same time, in many continental regions of the world, there are deposits with hyperenrichment of quartz veins in gold ("bonanza" ores, "bonanza" veins) [4,5] The concentration of gold in river water is 0.0001 µg/L, and in the ocean it is 0.00002 µg/L or 0.0000001 µmol/L [6].…”
Section: Introductionmentioning
confidence: 99%